Analepsis: “Retrospection” or an “Excursion into the Past”? - Efimenko, Aleksandr (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
Possible motivations for analepsis as a plot-shaping device are analyzed in the paper. In the Russian scholarship this device is interpreted either as retrospection introduced by remembrances, or as an excursion into the past conditioned by auctorial activity. An analysis of Yuri Polyakov’s novella Apofegei, supported by references to other Russian works, demonstrates that to motivate analepsis not only remembrance but also many other devices are used, such as introducing a new referent, anadiplosis of informative contexts, or an announced message. That is why the author of the paper proposes to use along with the terms retrospection and excursion into the past also the terms dominant analepsis and non-dominant analepsis. It is underlined that both the retrospection built on basis of a character’s remembrances and excursions into the past produced by the narrator’s constructing activity can be used within the frames of dominant and non-dominant analepses.